A narrative review on the applications of intracavitary contrast-enhanced ultrasonography in pediatric lower genitourinary anomalies - Jiayu Ren; Ting Ma; Shuyan Huang; Gongquan Chen; Christoph F. Dietrich; Yuexiang Peng; Xinwu Cui (Frontiers Media S.A., 2023)
PurposeWe mainly aimed to perform a narrative review of clinical applications of the three intracavitary contrast-enhanced ultrasonography (CEUS) including contrast-enhanced voiding urosonography (ceVUS), contrast-enhanced retrograde urethrosonography (ceRUG), and contrast-enhanced genitosonography (ceGS) in pediatric lower genitourinary anomalies.MethodA literature search in the PubMed and Web of Science databases was conducted up to 1 July 2022 on all studies published in English using the search terms "contrast-enhanced voiding urosonography", "contrast-enhanced retrograde urethrosonography", and "contrast-enhanced genitosonography". Trials were limited to pediatric subjects (ages ≤18 years) with no time restrictions. The inclusion criteria were studies on ceVUS, ceRUG, and ceGS to evaluate pediatric lower genitourinary anomalies. Two independent authors summarized the included articles.ResultsFinally, a total of 48 original articles and 6 case reports or case series were included, of which 50 (93%) were only relevant to ceVUS, 3 (5%) articles involved ceGS, while only one (2%) article involved ceRUG, and 87% of the applications of ceVUS were focused on vesicoureteral reflux (VUR). We also searched 24 related reviews, of which 20 involved ceVUS in diagnosing VUR and 4 involved ceRUG and ceGS for other lower genitourinary anomalies.ConclusionIntracavitary CEUS including ceVUS, ceRUG, and ceGS in pediatrics has many advantages over other radiological examinations in diagnosing lower genitourinary anomalies. Although ceVUS is widely used in detecting VUR, ceRUG and ceGS have also become promising techniques for evaluating the urethral pathologies and urogenital sinus.